Biophysicochemical Variability Evaluation of Jatropha curcas L. Collections for Biodiesel Feedstock: Jutropha curcas as Biodiesel Feedstock (Biological Sciences - PJSIR, 2010)
The seed oils of six Jatropha curcas biotypes were evaluated for their oil quality parameters and showed: oil content (38-41 %), acid value (0.14-6.94 mg/g), free fatty acid (0.07-3.47 %), iodine value (115.48-163.37 mg/g) and viscosity (0.6320-0.7431). Significant differences among biotypes were observed in oil yield and biochemical param- eters. The variability among the biotypes indicate a good scope of genetic  gain  through    selection.